2007
DOI: 10.1021/la7012705
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot-Insect Neuropeptide Conjugates for Fluorescence Imaging, Transfection, and Nucleus Targeting of Living Cells

Abstract: We identified an insect neuropeptide, namely, allatostatin 1 from Drosophila melanogaster, that transfects living NIH 3T3 and A431 human epidermoid carcinoma cells and transports quantum dots (QDs) inside the cytoplasm and even the nucleus of the cells. QD-conjugated biomolecules are valuable resources for visualizing the structures and functions of biological systems both in vivo and in vitro. Here, we selected allatostatin 1, Ala-Pro-Ser-Gly-Ala-Gln-Arg-Leu-Tyr-Gly-Phe-Gly-Leu-NH2, conjugated to streptavidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 81 publications
1
76
0
2
Order By: Relevance
“…Size-tunable fluorescence emission from UV to near infrared; sensitivity to charge and excellent photosensitizers [35,36,[69][70]85,89,110,115,[122][123] Oxides Iron oxide Magnetic properties for MRI Magnetic contrast properties [71][72]75,83,[91][92][93]98] Polymers Poly(lactic-co-glycolic acid), poly(amido amine) and dendrimers Biocompatibility, biodegradability and controlled release…”
Section: Cellular Delivery Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Size-tunable fluorescence emission from UV to near infrared; sensitivity to charge and excellent photosensitizers [35,36,[69][70]85,89,110,115,[122][123] Oxides Iron oxide Magnetic properties for MRI Magnetic contrast properties [71][72]75,83,[91][92][93]98] Polymers Poly(lactic-co-glycolic acid), poly(amido amine) and dendrimers Biocompatibility, biodegradability and controlled release…”
Section: Cellular Delivery Of Nanoparticlesmentioning
confidence: 99%
“…Ast 1 (APSGAQRLYGFGL) was identified as a member of a family of 13 neuropeptides that are widely distributed in insects and crustaceans whose receptors are highly homologous to somatostatin and galanin receptors [121]. In 2007, Biju et al identified the peptide's ability to mediate the rapid uptake of commercial streptavidinconjugated QDs after its assembly onto the QD via an avidin-biotin interaction linkage [122]. In NIH 3T3 and A431 cells the QDs were endocytosed and localized primarily within the endosomal compartment upon initial uptake.…”
Section: Neuropeptidementioning
confidence: 99%
“…Th erefore, metal nanoparticles could be an improved option for insecticides. It has been reported that nanomaterials possess insecticidal properties (Simonian et al 2005;Biju 2007;Rai et al 2012;Chakravarthy et al 2012). Furthermore, metal nanoparticles are essential components of new biosensors and self--assembled nanodevices (Levy et al 2006;Hsing et al 2007;Bhattacharyya et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…7,8,1518,25 The screening of efficiency of siRNA is realized by measuring the FRET signal between QDs-labeled siRNA and Cy5-labeled mRNA as shown in Figure 11. We designed and synthesized several sequences of siRNA, of which sequences are complementary to the sequences of BCR-ABL fusion gene.…”
Section: Biomedical Applications Of Quantum Dotsmentioning
confidence: 99%